Catcalling Sebagai Dampak Budaya Patriarki Dalam Bingkai Analisis Gender, Sexuality, and The State In Southeast Asia karya Michael G. Peletz - sahri, mat; Pramana, Gede Indra; Noak, Piers Andreas (Jurnal Nawala Politika, 2023)
Gender and sexuality issues are currently still a concern not only in Indonesia, but in various countries around the world. According to Michael G. Peletz, women from various social classes are involved in political, economic, and religious changes which are characterized by underlying similarities and forged in cultural practices, identities, and subjectivity. The process of gender bias from historical times, the old order, the new order, reforms, until now continues to experience changes in form. Gender relations become unbalanced due to patriarchy. Currently, the term is used to refer to male power, to power relations, where men are at a higher level than women, and is a feature of a system in which women continue to be degraded using many means, one of which is sexual harassment. Patriarchal culture that is not addressed wisely in the modern era is now a problem because there is an ambiguity of meaning in society about catcalling as a joke or sexual harassment, especially against women.